A RESEARCH ON PHARMACUETICAL PREPARATION OF TAMRA GARBHA POTTALI - Himabindu,; Ravi Chavan,; M.S.Doddamani, (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda a science of life bloomed on its own concepts of health maintenance and curative aspects. One of the prenomial off shoot of Ayurveda is Rasashastra, an Indian alchemy. Pottali kalpana is a peculiar pharmaceutical dosage form, is unique in terms of its preparation, mode of administration, quick in action, less dose and easy for transportation. Tamra Garbha pottali (TMGP) is one such herbo-mineral-metallic complex formulation containing Tamra bhasma (T.B), Shodita Swarna, Hingulotta Parada and Shodhit Gandhaka. Among the different pharmaceutical methods, Gandhaka paka method is considered to be the best method to enhance the properties of the drugs and to keep them in a concise form.Pilot study of 6 Pottalis was conducted to standardize the temperature required to do Pottali paka and to assess the Pottali siddi lakshanas like Vyoma varna of Gandhaka paka, hardness of Pottali and changes of silk cloth tied to the Pottali. The main study conducted in 2 batches on the standards made by the pilot study. Observations made on the time duration required for the study, temperature to be given to Paka, changes in the Gandhaka varna till attainment Vyoma varna noted. The Study gave standard pharmaceutical method of Pottali paka w.s.r to Tamra garbha pottali.